Modification of graphene oxide by curcumin and application in polyurethane coating - Nguyen, Thuy Duong; Tran, Boi An; Phan, Thanh Thao; Vu, Ke Oanh; Nguyen, Anh Son; Nguyen, Tuan Anh; Thi Xuan Hang, To (Vietnam Journal of Science and Technology, 2020)
Curcumin modified graphene oxide (GO-CR) was prepared using adsorption method and polyurethane (PU) coating containing 0.3 wt% GO-CR was prepared on carbon steel. Synthesized GO-CR was characterized by fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM) and zeta potential measurement. Corrosion protection property of polyurethane coating containing GO-CR was evaluated and compared with blank polyurethane coating and coating containing GO by electrochemical impedance spectroscopy. The results showed that GO-CR has layer structure like GO with lower crystallinity. In GO-CR structure curcumin was attached on GO surface. The presence of curcumin on GO-CR surface provided corrosion inhibition action for PU coating and also improved the dispersion of GO in PU coating.